Self Efficacy Nenek dalam Pemberian ASI eklusif pada Ibu Menyusui Bayi usia 1-6 Bulan dengan Pendekatan Health Promotion Model - Heri wibowo; Ririn probowati; Abdul muhith; Monika Savitri; khamidah khamidah (Universitas Nahdlatul Ulama Surabaya, 2019)
The importance of grandmother's competence in breastfeeding also greatly influences the success of mother's breastfeeding to her baby. Yukensi (Paguyuban Kakek Nenek ASI) is an association or association that has members consisting of Grandparents and Grandmothers who are in charge of ASI support groups The study design was cross sectional. Research variables: grandmother's self efficacy, grandchild age, number of children, number of grandchildren and grandchildren age. Active grandmother sample came at POSYANDU elderly Ngelele village, Sumobito sub-district, Jombang regency 2018 number 68 using simple romdom sampling and analyzed by Chi-square test with α = 0.05 . Data collection from September to October 2018. The results of the study almost half (47%) had sufficient self efficacy, some at the age of 40-65 years. Most (87.5%) self efficacy is enough with the number of children> 2-4 children. Most (78.1%) self efficacy is enough with the number of grandchildren 2-4 children. Most (78.1%) self efficacy is enough with grandchildren> 6 months. All variables have a strong influence on self-efficacy on the variable number of children and grandchildren. Other variables have a weak relationship. Variable number of children and the age of grandchildren who live in the house. Self efficacy is influenced by personal experiences that have been traversed in the form of success and failure. A grandmother who has experience in caring for her child can provide exclusive breastfeeding will increase her self efficacy in providing assistance to her child (mothers who are breastfeeding) so that their children provide exclusive breastfeeding with more than one child and grandchildren more than 6 months will make a grandmother have self good efficacy. Besides self-efficacy experience can be improved through Verbal persuasion that can be done repeatedly. Keywords: grandmother's self-effecacy, exclusive breastfeeding